2014
DOI: 10.1186/1477-7819-12-360
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological features of five-year survivors after pancreatectomy for pancreatic adenocarcinoma

Abstract: BackgroundClinical factors determining short-term survival after pancreatectomy have been well studied, but factors predicting long-term survival with curative resection are poorly understood in pancreatic carcinoma. Our objective was to identify clinical and pathological features of five-year disease-free survivors after surgical resection of pancreatic adenocarcinoma.MethodsThe clinical and pathological data from 147 patients who underwent a potentially curative resection for pancreatic adenocarcinoma at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 27 publications
7
37
1
4
Order By: Relevance
“…CA19-9, CEA, SPan-1, and DUPAN-2 have also been reported to be useful and prognostic factors for PDAC [15, 23, 24]. In this study, we identified CA19-9 and CEA as independent predictors of early recurrence after pancreatic resection in PDAC patients.…”
Section: Discussionmentioning
confidence: 50%
“…CA19-9, CEA, SPan-1, and DUPAN-2 have also been reported to be useful and prognostic factors for PDAC [15, 23, 24]. In this study, we identified CA19-9 and CEA as independent predictors of early recurrence after pancreatic resection in PDAC patients.…”
Section: Discussionmentioning
confidence: 50%
“…Only 20% of patients with pancreatic cancer are candidates for potentially radical resection [2]. Surgical resection is associated with a median OS of 11 to 23 months and with a 5-year OS of about 20% [3, 4]. Furthermore, 60% of patients experience local and systemic relapse within the first 12 months after curative surgery [3].…”
Section: Introductionmentioning
confidence: 99%
“…A quarter of patients have a locally advanced disease with approximately 53% of patients presenting with distant metastases. Several studies have analysed the prognostic factors of long-term survival and evaluated the 5-year survival in resected patients [6][7][8][9][10][11][12][13][14][15] (Tables 1 and 2). …”
Section: Introductionmentioning
confidence: 99%